Inside Cover: Porous Covalent Organic Polymers for Efficient Fluorocarbon‐Based Adsorption Cooling (Angew. Chem. Int. Ed. 33/2021). Issue 33 (21st June 2021) - Zheng, Jian; Wahiduzzaman, Mohammad; Barpaga, Dushyant; Trump, Benjamin A.; Gutiérrez, Oliver Y.; Thallapally, Praveen; Ma, Shengqian; McGrail, B. Peter; Maurin, Guillaume; Motkuri, Radha Kishan
Abstract : Defective covalent organic polymers are promising for adsorption‐based cooling applications. In their Research Article on page 18037, Guillaume Maurin, Radha Kishan Motkuri, and co‐workers present experimental and computational evidence that mesoporous defects in the framework play a key role for the unique overall linear‐shaped R134a adsorption isotherm and the exceptional adsorption uptake.